Exploring supplier–supplier innovations within the Toyota supply network: A supply network perspective - Potter, Antony; Wilhelm, Miriam (Journal of Operations Management, 2020)
AbstractThis article investigates the development of supplier–supplier innovations that occur when two firms that are part of the same supply network co‐patent a new product. This study unravels how the structure of the supply network influences each firm's ability to form supplier–supplier innovations with other network members. Specifically, we investigate how supplier degree centrality influences the generation of supplier–supplier innovations, and the extent to which this relationship is moderated by the structural embeddedness of firms in the supply network. Using data from the Toyota supply network, the results reveal that a firm's ability to co‐develop supplier–supplier innovations with other network members depends on its number of ties and their direction within the supply network. Although betweenness centrality has no significant moderating effect, closeness centrality, and embeddedness in small world clusters negatively moderate the relationship between supplier degree centrality and supplier–supplier innovations. Additionally, the number of manufacturing plants a firm operates in Japan strengthens the positive effect supplier degree centrality has on the development of supplier–supplier innovations.